2011
DOI: 10.1007/s10900-011-9472-5
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Waterborne Diseases: Analysis of a Community Health Worker Program in Rural Tamil Nadu, India

Abstract: Community health worker (CHW) programs have become popular tools in reducing the burden of childhood illnesses. However, the efficacy of CHWs in facilitating behavior change, as a means of preventing waterborne diseases, remains unclear. Using a household survey (n = 225),in rural Tamil Nadu, South India, we assessed the effects of a CHW program on knowledge, attitudes and practices related to diarrheal illness through comparison with a control population that was not enrolled in the program. The CHW program i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Educational attainment was the only significant predictor of accurate disease prevention strategies or knowledge [10,11]. UNICEF observed that the sanitation and hygiene promotion based on community participatory approaches could lead to significant reduction of diarrhea in children in Turkana district in Kenya [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Educational attainment was the only significant predictor of accurate disease prevention strategies or knowledge [10,11]. UNICEF observed that the sanitation and hygiene promotion based on community participatory approaches could lead to significant reduction of diarrhea in children in Turkana district in Kenya [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A study in tribal areas of Odisha concluded that after the awareness campaign about mosquito bites, most participants adopted the recommended preventive measure of using insecticide treated bed nets (ITBN) 12 . In rural Tamil Nadu, awareness generation to waterborne diseases left gaps in understanding the connection between using contaminated drinking water and disease 13 . Finally, in high chikungunya prevalent areas in urban India, there was no significant association between respondents’ education level and emptying/drying of water containers 14 .…”
mentioning
confidence: 99%